Hematological parameters of Brycon amazonicus (Bryconidae) broodstock in captivity - Paola Gonzales, Anai (2019)
The objective of this study was to determine the hematological values of Brycon amazonicus broodstock under culture in Iquitos, Peru. Blood samples were taken from 12 specimens (1.62 ± 0.45 kg and 51.38 ± 2.93 cm) maintained in earthen ponds and fed twice a day with a commercial diet with 22% crude protein. The fish were collected with a net and anesthetized with eugenol. Blood extraction was performed with disposable syringes containing EDTA (10%). The values obtained from the erythrocytic series were: hematocrit 53.3 ± 4.8%; hemoglobin 20.1 ± 3.2 g/dl; erythrocytes 2.8 ± 0.5 x106/μl; VCM 194.4 ± 54.4 fl; CHCM 37.7 ± 4.8 g/dl; HCM 72.6 ± 17.7 pg. The number of leukocytes was 8.1 ± 6.0 x103/μl. In the differential count of leukocytes, the lymphocytes and monocytes had greater proportion in comparison with neutrophils, eosinophils and basophils. The total serum protein was 3.7 ± 0.4 g/dl and the glucose was 60.2 ± 39.1 mg/dl. The values found for B. amazonicus were compared with other species of the genus Brycon showing some variations, but within the range reported for teleost fishes.